"A experiência de psicólogos/artistas" - Abranches, Maria Stella Dunshee de (2001)
Human experience s complexity and plurality, which demands questionning on possible articulations of contemporary clinical psychology and other areas of knowledge, builds up this work s scenary which aims to get acquainted with and transmit the psychologist/artists experience. Based on her own experience as a singer and as a psychology therapist, the researcer runs over other psychologists/artists narratives to through them investigate some possible articulationns between these two practices . In order to reach the proposed objectives, the author circumscribes both experiencing and transmission, by means of the narratives, in Gendlin s and Benjamin s works, in search of a theoretical basis needed to validate them as knowledge s production and transmission elements. Then she gives a brief description of the role of narratives in psychotherapy according to Goolishian s and Anderson s postmodern view. Finally, after presenting the psychologists/artists s narratives, she deepens her initial questionning by going through a dialog between her understanding of the research participants experience and the theoretical references which guide her final appreciation